Investigating Co-Constructive Behavior of Large Language Models in Explanation Dialogues - Fichtel, Leandra; Spliethöver, Fichtel; Hüllermeier, Eyke; Jimenez, Patricia; Klowait, Nils; Kopp, Stefan; Ngonga Ngomo, Axel-Cyrille; Robrecht, Amelie; Scharlau, Ingrid; Terfloth, Lutz; Vollmer, Anna-Lisa; Wachsmuth, Henning
The ability to generate explanations that are understood by explainees is the quintessence of explainable artificial intelligence. Since un- derstanding depends on the explainee’s back- ground and needs, recent research focused on co-constructive explanation dialogues, where an explainer continuously monitors the ex- plainee’s understanding and adapts their expla- nations dynamically. We investigate the ability of large language models (LLMs) to engage as explainers in co-constructive explanation dia- logues. In particular, we present a user study in which explainees interact with an LLM in two settings, one of which involves the LLM being instructed to explain a topic co-constructively. We evaluate the explainees’ understanding be- fore and after the dialogue, as well as their perception of the LLMs’ co-constructive behav- ior. Our results suggest that LLMs show some co-constructive behaviors, such as asking ver- ification questions, that foster the explainees’ engagement and can improve understanding of a topic. However, their ability to effectively monitor the current understanding and scaffold the explanations accordingly remains limited.

Role Perception Questionnaire: Co-construction. Scales manual - Buhl, Heike M.; Fisher, Josephine Beryl; Rohlfing, Katharina J.

SFS-gestützte Synthese von Katalysatorpartikeln zur selektiven katalytischen Reduktion von NOx - Beimdiek, Janis; Schmid, Hans-Joachim

Influence of surface impurities on the catalytic activity of nanoparticles synthesized by a spray flame synthesis (oral presentation) - Beimdiek, Janis; Schmid, Hans-Joachim

Selektive katalytische Reduktion von NOx an gasphasensynthetisierten Katalysatorpartikeln (Vortrag) - Beimdiek, Janis; Schmid, Hans-Joachim

Ultrafast Electron Dynamics at the Water‐Modified InP(100) Surface - Diederich, Jonathan; Paszuk, Agnieszka; Ruiz Alvarado, Isaac Azahel; Krenz, Marvin; Zare Pour, Mohammad Amin; Babu, Diwakar Suresh; Velazquez Rojas, Jennifer; Höhn, Christian; Gao, Yuying; Schwarzburg, Klaus; Ostheimer, David; Eichberger, Rainer; et al. (Advanced Materials Interfaces)
Abstract The interaction of water molecules with semiconductor surfaces is relevant to various optoelectronic phenomena and physicochemical processes. Despite advances in fundamental understanding of water‐exposed surfaces, the detailed time‐ and energy‐resolved behavior of excited electrons remains largely unexplored. Here, the effects of water exposure on the near‐surface electron dynamics of phosphorus‐terminated p(2×2)/c(4×2)‐reconstructed indium phosphide (100) (P‐rich InP) are studied experimentally and matched to theoretical calculations. The P‐rich InP surface, consisting of H‐passivated P‐dimers, serves as a model for other P‐containing III‐V semiconductors such as gallium phosphide (GaP) or aluminum indium phosphide (AlInP). Electron dynamics near the surface are probed with femtosecond resolution using time‐resolved two‐photon photoemission (tr‐2PPE), a pump‐probe spectroscopic technique. Pulsed water exposure preserves electronic states and significantly increases lifetimes at the conduction band minimum (CBM). Density‐functional theory (DFT) calculations attribute these findings to suppression of surface vibrational modes in the top P‐layer by water exposure, reducing electronic transition probabilities of near‐band‐gap surface states. The results suggest that many near‐surface state lifetimes reported in ultra‐high vacuum may change significantly upon electrolyte exposure. These states may thus contribute more strongly to surface reactions than traditionally assumed. Demonstrating this effect for the technologically relevant P‐rich InP surface opens new opportunities in this underexplored area of surface electrochemistry.

Untersuchung des Einflusses der Zusammensetzung von Lösungsmitteln und Gasen bei der Herstellung nanoskaliger Eisenoxide mittels Sprühflammensynthese - El Gabbouhi, Abderazzak; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Topological defects in semiconducting carbon nanotubes as triplet exciton traps and single-photon emitters - Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero (Nanoscale)
First-principles calculations reveal how topological defects in semiconducting carbon nanotubes trap triplet excitons and enable single-photon emission at telecom wavelengths, offering new insights into their potential for photonic devices.

Planning a Swarm-Based Mobility System with Autonomous Vehicles for Sustainable and Flexible Transportation in Rural Areas - Stumpe, Miriam; Speckenmeyer, Philipp; Schryen, Guido; Kleinjohann, Lisa; Weskamp, Christoph (Proceedings of the Thirty-first Americas Conference on Information Systems (AMCIS 2025))

The Impact of Chatbot Familiarity and Frequency of Use on Human-Likeness - Göbel, J.; Betke, H.; Boldt, J.; Tran, M. L.; Schryen, Guido (Proceedings of the Thirty-first Americas Conference on Information Systems (AMCIS 2025))

Theory of Multimode Squeezed Light Generation in Lossy Media - Kopylov, Denis A.; Meier, Torsten; Sharapova, Polina R. (Quantum)
A unified theoretical approach to describe the properties of multimode squeezed light generated in a lossy medium is presented. This approach is valid for Markovian environments and includes both a model of discrete losses based on the beamsplitter approach and a generalized continuous loss model based on the spatial Langevin equation. For an important class of Gaussian states, we derive master equations for the second-order correlation functions and illustrate their solution for both frequency-independent and frequency-dependent losses. Studying the mode structure, we demonstrate that in a lossy environment no broadband basis without quadrature correlations between the different broadband modes exists. Therefore, various techniques and strategies to introduce broadband modes can be considered. We show that the Mercer expansion and the Williamson-Euler decomposition do not provide modes in which the maximal squeezing contained in the system can be measured. In turn, we find a new broadband basis that maximizes squeezing in the lossy system and present an algorithm to construct it.

Who are the Actively Participating Crowdworkers? A Qualitative Comparative Analysis of a German Text Creation PlatformSocio-Economic Studies, - Schneider, Martin; Hemsen, Paul; Kundisch, Dennis (management revue - Socio-Economic Studies, Special Issue “Digital Transformation of Work”.)

Traffic Scenario Detection – A Comparison of CNN-RNN and Transformer-based Architectures in the Context of Autonomous Driving - Grieger, Nicole; Okumus, Hasan; Burdorf, Sven; Kundisch, Dennis (Proceedings of the MCIS 2025)

Tech, Trash and Theft – Exploring the Impact of Food Waste Apps on Local Shoplifting in Grocery Stores and Supermarkets - Althaus, Maike (Proceedings of the MCIS 2025)

KI-gestützter Umgang mit Textprodukten im prozessorientierten DaF-Unterricht. - Ballweg, Sandra (Erträge des JGG-Seminars für Deutsch als Fremdsprache Leistungsbeurteilung und Schreibprodukte)

Female Reproductive Bodies and the Shift from Risk to Threat Society: The (Mis)Use of the Powers of Pregnancy in Margaret Atwood’s The Handmaid’s Tale and Amy Ewing’s The Lone City-Series - Schneider, Julia Christina (Women and Their Body)

"man hat sich halt online getroffen". Zur Aushandlung räumlicher Praktiken in virtuellen Austauschbegegnungen. - Ballweg, Sandra (Fremdsprachenlehren und -lernen zim Spannungsfeld von digital und analog)

Civic Vice in Digital Governance - Reijers, Wessel (Public Governance and Emerging Technologies)
Abstract It has become a new global trend that governments are partially automating decision-making processes by public agencies. This, however, has led to some scandals revealing grave injustices, including the Robodebt scandal in Australia and the childcare benefit scandal in the Netherlands. This chapter argues that the normative impacts of the move towards automated decision-making can be fruitfully understood and addressed through the lens of civic virtue. It starts by outlining the Dutch childcare benefit scandal, showing that what happened cannot be reduced solely to human intent or structural factors, but needs to address the in-between term of human moral dispositions. Following this insight, the chapter outlines a framework of civic virtue, which outlines ideal states (civic virtue) and their deviations (civic vice) for different temporal configurations (past-, present-, and future-oriented civic virtue). Finally, the chapter uses this framework to reflect on the much-touted principle of ‘explainability’ in addressing harms like the ones done to citizens in the childcare benefit scandal. Three impacts are laid bare through the lens of civic virtue, of servility, presumptuousness, and political recalcitrance. Explainability, the chapter argues, may successfully address these impacts, but only if it ceases to focus solely on narrow black box problems in AI and address public governance more holistically.

"FiBSS - Fortschritt in und durch Bewegung, Spiel und Sport im Grundschulganztag" - eine Qualifizierung für das pädagogische Personal im Ganztag - Satzinger, Nicole; Fögen, Yvonne; Noetzel, Ida; Kehne, Miriam (Handbuch Bewegung und Sport in der Sozialen Arbeit)

Bewegung und Sport in der Ganztagsschule - Kehne, Miriam; Fögen, Yvonne; Satzinger, Nicole; Noetzel, Ida (Handbuch Bewegung und Sport in der Sozialen Arbeit)